Assessing the relationship between perceived crowding, excitement, stress, satisfaction, and impulse purchase at the retails in Vietnam - Van Dat Tran (Taylor & Francis Group, 2020)
This study aims to examine the relationship between perceived crowding, excitement, stress on satisfaction, and impulse purchase at the retails in Vietnam. This study performed structural equation modelling (SEM). A total of 264 valid respondents were used in this research. Besides, this study systematized the concept, defined, and test the component scales of the relationship model among perceived crowding, excitement, stress, satisfaction, and impulse purchase from the collected data, which helps to identify the relationship among factors in the model as well as impact. The findings indicate that the perceptions of human and spatial crowding have a negative influence on customer satisfaction leading to their impulse purchase decision. This belief is advocated by the existence of human emotional reactions to customer satisfaction. In detail, exciting reactions positively impact on shoppers’ satisfied feelings; by contrast, stress is negatively related to customers’ satisfaction. In other words, shoppers intend to be more excited and less stressed in retail who could facilitate a low level of spatial crowding and appropriate physical arrangements of fixtures.